Linguistic Decision Making Theory and Methods - Xu, Zeshui; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg : Imprint: Springer, 2012)
"Linguistic Decision Making: Theory and Methods" is the first monograph which mainly deals with the interdisciplinary subject of computing with words, information fusion and decision analysis. It provides a thorough and systematic introduction to the linguistic aggregation operators, linguistic preference relations, and various models for and approaches to multi-attribute decision making with linguistic information. It also offers various practical examples with tables and figures to illustrate the theory and methods discussed. Researchers and professionals engaged in the relevant fields will find it a useful reference book. Professor Zeshui Xu, senior member of the IEEE, works at the PLA University of Science and Techology, China.
Linguistic Evaluation Scales -- Linguistic Aggregation Operators -- Linguistic Preference Relations -- Approaches to Linguistic Multi-Attribute Decision Making.
Keywords: Mathematics; Data mining; Electronic data processing; Mathematical optimization; Operations research; Mathematics; Applications of Mathematics; Computing Methodologies; Operation Research/Decision Theory; Optimization; Data Mining and Knowledge Discovery